F. Botton Beja (2019). Ensayos sobre China. Una antología. México: El Colegio de México. 380 pp. - Ríos, María Elvira (Estudios de Asia y África, 2019)
F. Botton Beja (2019). Ensayos sobre China. Una antología. México: El Colegio de México. 380 pp.